2023
DOI: 10.1101/2023.04.14.536836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recursive self-embedded vocal motifs in wild orangutans

Abstract: Recursive procedures that allow placing a vocal signal inside another of similar kind provide a neuro-computational blueprint for syntax and phonology in spoken language and human song. There are, however, no known vocal patterns among nonhuman primates arranged in self-embedded combinations that evince vocal recursion or potential insipient forms and neuro-procedures thereof, suggesting a neuro-cognitive transformation exclusive to humans. Here, we uncover that wild flanged male orangutan long calls show two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Lar gibbons (Hylobates lar) studied in Thailand showed a single prominent rhythmic category corresponding to 1:1 (isochrony) [14]. The study of orangutans showed how these apes exhibited nested degrees of isochrony during their long calls [15].…”
Section: Small-ratio Rhythms Across Primatesmentioning
confidence: 99%
“…Lar gibbons (Hylobates lar) studied in Thailand showed a single prominent rhythmic category corresponding to 1:1 (isochrony) [14]. The study of orangutans showed how these apes exhibited nested degrees of isochrony during their long calls [15].…”
Section: Small-ratio Rhythms Across Primatesmentioning
confidence: 99%